Role of diet and nutrition treatment methods in reducing the ailment of the irritable bowel syndrome - Radosław Jerzy Balwierz; Karol Jasiński; Marcin Osowski; Kamil Grela; Ewa Karpęcka-Gałka; Anna Kusakiewicz-Dawid; Urszula Skotnicka-Graca (Polish Pharmaceutical Society, 2021)
The symptoms of irritable bowel syndrome are estimated in 10-20% of the population, and the disease is currently one of the most common diseases of the digestive system. Thus, it is a significant diagnostic problem for doctors and nutritionists in terms of the selection the appropriate diet therapy and for pharmacists in terms of potential pharmaceutical care and consultation on basic nutritional errors. Research shows that the prevalence of IBS contributes to a significant deterioration in the quality of life, and the type of food consumed has a significant impact on the well-being and health of the patient. The prevelance of symptoms is strongly related to the food consumed. About 60% of patients diagnosed with Irritable Bowel Syndrome notice an exacerbation in symptoms and a deterioration of well-being soon after eating a meal. Among them, 28% of people report symptoms as early as 15 minutes after eating, while in over 93% of patients, severe symptoms persist for about 3 hours after stopping eating. The main treatments for IBS are diet modification and pharmacotherapy. Diet modification consists in temporarily eliminating the intake of certain foods (e.g. containing fermentable carbohydrates, lactose, gluten) or increasing the intake of dietary fiber or short-chain fatty acids. The Low-FODMAP diet draws particular attention in the nutritional treatment of irritable bowel syndrome.Its main assumption is the elimination of fermentable components in the intestinal lumen, which significantly reduces the symptoms of IBS. Medical data do not give a clear answer about the effectiveness of the Low-FODMAP diet, indicating many inaccuracies in the methodology of the conducted research, as well as pointing to the potential bias of the results. However, it seems paausible to say that the diet seems to be effective for the relief of single symptoms (abdominal pain, flatulence). An improperly implemented Low-FODMAP diet can induce deficiencies of certain vitamins and minerals and reduce the diversity of the bacterial microflora. Unfortunately, it is disturbing that, according to statistics, only 21% of doctors recommend that their patients consult a dietitian for nutrition, and there is no objective data in the field of pharmacy advice. The aim of the work was to present the principles and assumptions of the Low-FODMAP diet and dietary interventions that can be implemented in the treatment of IBS.